6. Pendekatan Penilaian Kontingensi untuk Mengukur Kesediaan Konsumen Membayar Harga Perbaikan Mutu Air Minum - Halimatus Sa’diyah (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2008)
abstrak Water service providers are often under pressure to improve the service quality without having expertise necessary to understand how valuable this improvement would be to their consumers. Moreover criticisms also arise since many master plans of water treatment technologies and their distribution systems are mostly engeneer-dominated supply side approach and neglect demographic and financial realities of their consumers. The long term goal of this research is to find a healthy and safe water supply management system so that water can be used to drink directly from the tap. Besides this long term goal, this research also have specially short term targets namely: (1) to estimate the consumers’ willingness to pay (WTP) for water quality improvement; (2) to indentify factors determining the WTP, and; (3) as a respond to the issue of safe dringking water from consumer’s side in the City of Mataram dan West Lombok Regency. Research was conducted by utilizing Contingent Valuation Method (CVM) by interviewing 600 respondents selected through stratified random sampling. Results concluded that: Households’ willingness to pay for the quality improvement of water service is 7,233 rupiah per month so that total WTP in 2007 is 4.7 billion rupiah. Five main factors, among others, that determine WTP are: Consumers’ perception on contaminants in their drinking water Gender, tariffs cateory access to other drinking water sources respondents’ education The financial sustainability of quality improvement program of drinking water requires an appropriate tariff level, more than that it can guarantee a high collection rate. It is therefore urgently needed a proper justification from both supply side and beneficiaries (demand side). WTP estimation produced by CVM can be seen as an important information from demand side. Although consumers’ WTP is relatively high, their low income per capita should be considered in setting a suitable tariff level.